Answer:
15
Step-by-step explanation:
5(2)(3)-2(2)+13+7(2)-6(2)(3)-4(2)+(2)(3)
30-4+13+14-36-8+6
15
see the attached figure to better understand the problem
we know that
1) If angle 1 and angle 2 are complementary angles
then
m∠1+m∠2=
------> equation A
2) If angle 1 and angle 2 are congruent angles
then
m∠1=m∠2 ------> equation B
Substitute equation B in equation A
m∠1+(m∠1)=
2m∠1=
m∠1=
therefore
<u>the answer is</u>
Answer:
A.) (7t³ + 2k^4)(7t³ - 2k^4)
Step-by-step explanation:
Factor the following:
49 t^6 - 4 k^8
49 t^6 - 4 k^8 = (7 t^3)^2 - (2 k^4)^2:
(7 t^3)^2 - (2 k^4)^2
Factor the difference of two squares. (7 t^3)^2 - (2 k^4)^2 = (7 t^3 - 2 k^4) (7 t^3 + 2 k^4):
Answer: (7 t^3 - 2 k^4) (7 t^3 + 2 k^4)
Answer:
2
Step-by-step explanation:
slope = difference of y/ difference of x
m = (9-5) / (4-2) = 4/2 = 2
3.33 repeating. if you look at it it's 2.70 what I would do is take away the zero for a minute and see how many times 9 goes into 27